The Barzanji Ritual in the Malay Tradition of the East Coast of Sumatra: Meanings, Symbols, and Local Variations - Fachri Syauqii; Syamsul Arifin (Mahesa Research Center (PT. Mahesa Global Publishing), 2025)
This study aims to analyze the Barzanji tradition among Malay communities in Riau, Jambi, Rantau Parapat, Aceh, and Deli Serdang in order to examine variations in practice and local specificities from the perspective of Islamic anthropology. Employing a qualitative method with a comparative approach, the research draws on participant observation, in-depth interviews with tradition and religious figures, and documentary analysis of Barzanji texts and ritual practices. The findings indicate that although Barzanji is grounded in relatively uniform textual structures, its enactment is adapted to diverse social and cultural contexts. In Riau, Barzanji functions as a symbol of Malay–Islamic tradition legitimacy; in Jambi, it reflects cultural flexibility and hybridity; in Rantau Parapat, it reinforces Islam–Malay identity within a multiethnic society; in Aceh, it demonstrates ritual institutionalization and collective performance; while in Deli Serdang, it represents a synthesis of sultanate traditions and community-based religious practices. These findings position Barzanji as an adaptive form of cultural da‘wah and contribute to scholarship in Islamic anthropology and Islam Nusantara by illustrating how religious rituals operate as arenas for negotiating identity, cultural authority, and the continuity of local Islamic traditions.